UPAYA GURU MENUMBUHKAN SIKAP EMPATI PADA ANAK DI TK PERINTIS 2 KABUPATEN KUBU RAYA - Ulfah, Suciati; R, Marmawi; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by empathy for children who are still undeveloped. This was what makes researchers curious about the efforts of teachers to cultivate empathy for children aged 5-6 years at TK Perintis 2. The general objective of this study illustrated the efforts of teachers to grow empathy for children aged 5-6 years at TK Perintis 2. This research used methods descriptive and qualitative approach. The data source consisted of 1 teacher in class B1 and 13 children. From the results of the study, it was found that the teacher's efforts to cultivate empathy for children aged 5-6 years at TK Perintis 2 used the storytelling method by conveying messages related to empathy, exemplary methods by modeling attitudes or behavior, lecture methods by verbally presenting related information about the message you want to convey. The teacher was expected to make an activity in the form of a picture guessing game that stimulates children to empathize. Parents and teachers must communicate more often to help children grow in empathy. Teachers also need to use habituation methods and tourism methods to grow children's empathy.Keywords: Empathy Attitude, Teacher Efforts